(untitled) (Annals of Medical Research, 2023)
Aim: Morphological variations in carpal bone may affect wrist pathologies. In this study, we examined the relationship between carpal bone morphologies and scaphoid fractures. Materials and Methods: Patients with a prominent scaphoid fracture on posteroanterior and ulnar deviation X-rays were included in the study. Morphological types of lunate, hamate, capitate, presence of capitate-fourth metacarpal joint, and scaphoid fracture location were documented retrospectively. A total of 68 patients, 65 (95.6%) male, and 3 (4.4%) female were included in the study. Results: Considering the scaphoid fracture types, 40 (58.8%) patients had waist fractures, and 28 (41.2%) patients had proximal pole fractures. The association of fracture type and morphology of carpal bones was examined. Conclusion: In our study, we found that lunate, capitate, hamatum morphology and ulnar variance, fourth metacarpal articulation did not affect the scaphoid fracture pattern.